A hyperplasticity model for clay behaviour: an application to Bangkok clay - Likitlersuang, S; S. Likitlersuang (2003)
The main purpose of this thesis is the development of a new constitutive soil model emphasising the use of thermodynamic principles. This new approach to plasticity modelling, termed ‘hyperplasticity’, was first developed by Collins and Houlsby (1997) and Houlsby and Puzrin (2000). This idea has been further extended to continuous hyperplasticity in which smooth transitions between elastic and plastic behaviour can be modelled (Puzrin and Houlsby, 2001b). Applying hyperplasticity to this research, a kinematic hardening model specified by means of two scalar functionals is used to accommodate the effect of stress history on stiffness. A rate-dependent calculation for an approximation of the incremental stress-strain response is introduced. The model developed in the research is named ‘kinematic hardening modified Cam-clay (KHMCC) model’ and requires eight parameters (plus an extra parameter for rate-dependent analysis). Triaxial test results from the Asian Institute of Technology (AIT) and cyclic undrained triaxial data from Chulalongkorn University are employed to establish the soil parameters for the new model. The model is initially developed in terms of triaxial stress-strain parameters for the purpose of comparison with the experimental data on Bangkok clay. The model is expressed in FORTRAN code for implementation into the OXFEM finite element program. Two examples of real geotechnical projects in Bangkok (a road embankment and tunnelling in soft ground) are analysed under plane strain conditions. Comparisons of the numerical analysis results with field data are made. In addition, factors affecting the results of the analysis such as stress history and K0, are investigated.